Advances in bacteriophage-mediated strategies for combating polymicrobial biofilms - Gliźniewicz, Marta; Miłek, Dominika; Olszewska, Patrycja; Czajkowski, Artur; Serwin, Natalia; Cecerska-Heryć, Elżbieta; Dołęgowska, Barbara; Grygorcewicz, Bartłomiej (Frontiers in Microbiology, 2024)
Bacteria and fungi tend to coexist within biofilms instead of in planktonic states. Usually, such communities include cross-kingdom microorganisms, which makes them harder to remove from abiotic surfaces or infection sites. Additionally, the produced biofilm matrix protects embedded microorganisms from antibiotics, disinfectants, or the host immune system. Therefore, classic therapies based on antibiotics might be ineffective, especially when multi-drug-resistant bacteria are causative factors. The complexities surrounding the eradication of biofilms from diverse surfaces and the human body have spurred the exploration of alternative therapeutic modalities. Among these options, bacteriophages and their enzymatic counterparts have emerged as promising candidates, either employed independently or in synergy with antibiotics and other agents. Phages are natural killers of bacteria, and due to different mechanisms of action than antibiotics might answer worldwide problems with bacterial infections. In this review, we report the attempts to use bacteriophages in combating polymicrobial biofilms in in vitro studies, using different models, including the therapeutical use of phages. Also, we sum up the advantages, disadvantages, and perspectives of phage therapy.